2015
DOI: 10.1007/s12010-015-1549-7
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Tobacco to Remove Mercury from Polluted Soil

Abstract: Tobacco is an ideal plant for modification to remove mercury from soil. Although several transgenic tobacco strains have been developed, they either release elemental mercury directly into the air or are only capable of accumulating small quantities of mercury. In this study, we constructed two transgenic tobacco lines: Ntk-7 (a tobacco plant transformed with merT-merP-merB1-merB2-ppk) and Ntp-36 (tobacco transformed with merT-merP-merB1-merB2-pcs1). The genes merT, merP, merB1, and merB2 were obtained from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Due to its elevated negative charge density, it has been suggested that poly-P could aid in the bioremediation of toxic trace elements, acting as a chelating agent for positively charged metals such as mercury or cadmium. Thus, transgenic plants that produce poly-P via the expression of bacterial PPKs have been constructed that showed an increased capacity for mercury accumulation ( Nagata et al, 2010 ; Chang et al, 2015 ). Similarly, recombinant E. coli strains with increased levels of poly-P as a result of PPK overexpression also decreased their sensitivity toward mercury and displayed an increased inorganic mercury accumulation ( Pan-Hou et al, 2002 ; Ruiz et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its elevated negative charge density, it has been suggested that poly-P could aid in the bioremediation of toxic trace elements, acting as a chelating agent for positively charged metals such as mercury or cadmium. Thus, transgenic plants that produce poly-P via the expression of bacterial PPKs have been constructed that showed an increased capacity for mercury accumulation ( Nagata et al, 2010 ; Chang et al, 2015 ). Similarly, recombinant E. coli strains with increased levels of poly-P as a result of PPK overexpression also decreased their sensitivity toward mercury and displayed an increased inorganic mercury accumulation ( Pan-Hou et al, 2002 ; Ruiz et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we performed a PCR using a plasmid p(merT merP -merB1-merB2-ppk) [14] as template (Figure 1). The expected DNA band appeared in the agarose gel (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The plasmid p(merT-merP-merB1-merB2-ppk) and pp(merTmerP-merB1-merB2-pcs1) were stored in our lab [14]. The gene ppk (GenBank accession number: D14445.1) in the plasmid pp(merT-merP-merB1-merB2-ppk) was from the the polyphosphate kinase (ppk) gene isolated from Enterobacter aerogenes [15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although clover and mustard had been selected for removing mercury from soil, the biomass of clover and mustard were small and they were not ideal plants for phytoremediation [4] [14]. Comparatively, tobacco is an ideal plant for constructing genetic-modifying plants for accumulating mercury [23]. The biomass of tobacco plant is large.…”
Section: Discussionmentioning
confidence: 99%